Web-Based Inventory Information System Design at Sahabat Store Using Rad Method - Syahri Al Faiz; Santoso, Agustinus Budi; Dewi, Maya Utami (Jurnal Ilmiah Sistem Informasi, 2025)
This study aims to design and develop a web-basedinventory information system to improve stockmanagement and transaction recording efficiency atToko Sahabat. The main issues faced include frequentcashier system failures resulting in manualtransactions, stock data inaccuracies, and delayedsales reporting. The research employed the RapidApplication Development (RAD) method to enable fastand iterative system development based on userfeedback. Key features include user management,automatic stock tracking, real-time transactionrecording, and sales reporting. Using PHP, MySQL,and Bootstrap, the system significantly improvesoperational efficiency, reduces stock recording errors,and accelerates reporting. Implementation of thissystem supports better data-driven decision-making forToko Sahabat.